(untitled) (Research, Society and Development, 2021)
Aging is a natural process, but the search for reversing the signs caused on the skin is increasing nowadays. With advancing age, anatomical changes are mainly the most sought after and manifest themselves quickly, thus contributing to people looking for aesthetic treatments that minimize these changes. Objective: To analyze the results related to the Percutaneous Collagen Induction technique and elucidate the Application components, in the process of facial rejuvenation, using topical Vitamin C. Methods: Searches were conducted through scientific articles found in the Google Scholar, Surgical and Cosmetic Dermatology, Pubmed and Scielo databases. Articles published between 2003 and 2015 were searched. Results: The technique is low cost and easy to apply when compared to other rejuvenation treatments on the market. The needle thickness for use is minimal (0.5 mm), and therefore it can be considered a painless treatment. The greater amount of permeated vitamin C facilitates the antioxidant action, thus fighting free radicals and aiding in neocollagenesis. Conclusion: Through the studies carried out, it is concluded that the microneedling technique combined with Vitamin C is effective for the permeation of the active and has positive effects against skin aging. Although studies have already shown beneficial results for these new treatments, there is still a lack of data and new research. Further research is recommended to elucidate the molecular mechanisms regarding the application of vitamin C associated with microneedling.